Genome assembly and gene expression in the American black bear provides new insights into the renal response to hibernation. (5th November 2018) - Srivastava, Anuj; Kumar Sarsani, Vishal; Fiddes, Ian; Sheehan, Susan M; Seger, Rita L; Barter, Mary E; Neptune-Bear, Selena; Lindqvist, Charlotte; Korstanje, Ron
Abstract: The prevalence of chronic kidney disease (CKD) is rising worldwide and 10–15% of the global population currently suffers from CKD and its complications. Given the increasing prevalence of CKD there is an urgent need to find novel treatment options. The American black bear ( Ursus americanus ) copes with months of lowered kidney function and metabolism during hibernation without the devastating effects on metabolism and other consequences observed in humans. In a biomimetic approach to better understand kidney adaptations and physiology in hibernating black bears, we established a high-quality genome assembly. Subsequent RNA-Seq analysis of kidneys comparing gene expression profiles in black bears entering (late fall) and emerging (early spring) from hibernation identified 169 protein-coding genes that were differentially expressed. Of these, 101 genes were downregulated and 68 genes were upregulated after hibernation. Fold changes ranged from 1.8-fold downregulation ( RTN4RL2 ) to 2.4-fold upregulation ( CISH ). Most notable was the upregulation of cytokine suppression genes ( SOCS2, CISH, and SERPINC1 ) and the lack of increased expression of cytokines and genes involved in inflammation. The identification of these differences in gene expression in the black bear kidney may provide new insights in the prevention and treatment of CKD.